Reduction of Survey Sites in Dialectology: A New Methodology Based on Clustering - Jeszenszky, Péter; Steiner, Carina; Leemann, Adrian (Frontiers in Artificial Intelligence, 2021)
Many language change studies aim for a partial revisitation, i.e., selecting survey sites from previous dialect studies. The central issue of survey site reduction, however, has often been addressed only qualitatively. Cluster analysis offers an innovative means of identifying the most representative survey sites among a set of original survey sites. In this paper, we present a general methodology for finding representative sites for an intended study, potentially applicable to any collection of data about dialects or linguistic variation. We elaborate the quantitative steps of the proposed methodology in the context of the ‘Linguistic Atlas of Japan’ (LAJ). Next, we demonstrate the full application of the methodology on the ‘Linguistic Atlas of German-speaking Switzerland' (Germ.: ‘Sprachatlas der Deutschen Schweiz’ - SDS), with the explicit aim of selecting survey sites corresponding to the aims of the current project ‘Swiss German Dialects Across Time and Space’ (SDATS), which revisits SDS 70 years later. We find that depending on the circumstances and requirements of a study, the proposed methodology, introducing cluster analysis into the survey site reduction process, allows for a greater objectivity in comparison to traditional approaches. We suggest, however, that the suitability of any set of candidate survey sites resulting from the proposed methodology should be rigorously revised by experts due to potential incongruences such as the overlap of objectives and variables across the original and intended studies, and ongoing dialect change.